2018
DOI: 10.3389/fimmu.2018.01367
|View full text |Cite
|
Sign up to set email alerts
|

Functional Plasticity of Gamma Delta T Cells and Breast Tumor Targets in Hypoxia

Abstract: Interactions between immune and tumor cells in the tumor microenvironment (TME) often impact patient outcome, yet remain poorly understood. In addition, the effects of biophysical features such as hypoxia [low oxygen (O2)] on cells within the TME may lead to tumor evasion. Gamma delta T cells (γδTcs) naturally kill transformed cells and are therefore under development as immunotherapy for various cancers. Clinical trials have proven the safety of γδTc immunotherapy and increased circulating γδTc levels correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 63 publications
(57 reference statements)
1
36
0
Order By: Relevance
“…Tumor-intrinsic mechanisms that have been identified to impair γδ T cell attack include the release of large amounts of prostaglandin E2 by tumor cells with strong expression of cyclooxygenase-2 (COX-2), 151 the activity of indoleamine-2,3-dioxygenase (IDO) and its metabolite kynurenine, 225 the release of galectin-3, 226 and the hypoxic tumor microenvironment. 227 Inhibitors for the respective pathways can enhance tumor killing by Vδ2T cells in vitro, and it seems reasonable to propose that these strategies can also work in vivo, given the availability of approved drugs such as COX2 inhibitors. In addition to galectin-3, other tumor-expressed galectins, such as galectin-9, also suppress T cell activation.…”
Section: Combination Matters: How To Improve γδ T Cell Therapymentioning
confidence: 99%
“…Tumor-intrinsic mechanisms that have been identified to impair γδ T cell attack include the release of large amounts of prostaglandin E2 by tumor cells with strong expression of cyclooxygenase-2 (COX-2), 151 the activity of indoleamine-2,3-dioxygenase (IDO) and its metabolite kynurenine, 225 the release of galectin-3, 226 and the hypoxic tumor microenvironment. 227 Inhibitors for the respective pathways can enhance tumor killing by Vδ2T cells in vitro, and it seems reasonable to propose that these strategies can also work in vivo, given the availability of approved drugs such as COX2 inhibitors. In addition to galectin-3, other tumor-expressed galectins, such as galectin-9, also suppress T cell activation.…”
Section: Combination Matters: How To Improve γδ T Cell Therapymentioning
confidence: 99%
“…Sieger et al showed that the hypoxia‐exposed γδT cells failed to lyse the MCF7 breast tumor cells exposed to hypoxia, which concurs with our observation. They attributed it to the reduced expression of NKG2D and MICA, which is an indirect effect of hypoxia [31]. A recent study demonstrated that oxygen pressure in the tumor microenvironment orchestrates an anti‐ and pro‐tumoral γδT cell equilibrium through tumor‐derived exosomes which inhibited γδT cells proliferation and anti‐tumor cytotoxicity [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, tumors in hypoxic environments begin to secrete soluble NKG2D ligands, rendering cd T cells incapable of killing these cells. 112 Having previously homed to target organs, adoptively transferred Vd1 + T cells should be capable of homing again to a target organ containing a tumor. Furthermore, protocols have been developed that allow the rapid expansion of highly cytotoxic donor Vd1 + T cells (DOT cells), which are able to control leukaemic cell growth.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%